Beta-band power modulation in the human hippocampus during a reaching task. (12th June 2020) - Del Campo-Vera, Roberto Martin; Gogia, Angad S; Chen, Kuang-Hsuan; Sebastian, Rinu; Kramer, Daniel R; Lee, Morgan B; Peng, Terrance; Tafreshi, Ali; Barbaro, Michael F; Liu, Charles Y; Kellis, Spencer; Lee, Brian
Abstract: Objective. Characterize the role of the beta-band (13–30 Hz) in the human hippocampus during the execution of voluntary movement. Approach. We recorded electrophysiological activity in human hippocampus during a reach task using stereotactic electroencephalography (SEEG). SEEG has previously been utilized to study the theta band (3–8 Hz) in conflict processing and spatial navigation, but most studies of hippocampal activity during movement have used noninvasive measures such as fMRI. We analyzed modulation in the beta band (13–30 Hz), which is known to play a prominent role throughout the motor system including the cerebral cortex and basal ganglia. We conducted the classic 'center-out' direct-reach experiment with nine patients undergoing surgical treatment for medically refractory epilepsy. Main results. In seven of the nine patients, power spectral analysis showed a statistically significant decrease in power within the beta band (13–30 Hz) during the response phase, compared to the fixation phase, of the center-out direct-reach task using the Wilcoxon signed-rank hypothesis test (p < 0.05). Significance. This finding is consistent with previous literature suggesting that the hippocampus may be involved in the execution of movement, and it is the first time that changes in beta-band power have been demonstrated in the hippocampus using human electrophysiology. Our findings suggest that beta-band modulation in the human hippocampus may play a role in the execution of voluntary movement.